Sistem Persediaan Stok Barang PT. Shinheung Indonesia Berbasis Web Menggunakan Framework Laravel - Agus Suwarno; Nika Ferawati (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The problem of data processing is still done manually using MS. Excel and paper media, so that the impact resulted in a lot of data accumulation and errors in data processing of the stock inventory system at PT. Shinheung Indonesia, the implementation of the stock inventory system was able to provide data according to the execution of transactions in each department. Expenditure of stock of goods in the area of each department where data is input manually which includes, input stock, request for goods, output stock, balancing actual stock. This study aims to optimize the inventory of goods accurately and create a stock inventory system of PT. Shinheung Indonesia to make data processing more effective and efficient. The company or department is easier to process and control the existing stock. This system uses an object oriented programming development method, namely the Laravel framework. The information system design uses the programming languages PHP, mysql, xampp, sublimeText3, Gitbash. This study only discusses the inventory system carried out in the MC (Material Control) department of PT. Shinheung Indonesia Research that optimizes inventory in real time and minimizes errors in input output, so that all departments can access goods data when transacting. Keywords: System, Inventory, Object Orientation, Method, Stock of Goods, Framework.